Surveying Christian Beliefs and Religious Debates in Post-War Britain - Clements, Ben.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2016)
Clements provides a detailed study of religious beliefs in British society, using a broad range of opinion poll and social survey data. Examining public opinion on religious-secular issues, this book provides a rich analysis of the belief and attitudes of social groups over time.
Keywords: Social sciences; Religion; Christianity; Religion and sociology; Sociology; Social Sciences; Sociology of Religion; Christianity; Religion and Society; Religious Studies, general; Social Aspects of Religion; Sociology, general; Electronic books